Relative shares and elasticities simplified: comment - Samuelson, Paul A. (American Economic Review, 1973)
Explains the taxonomy of changing factor shares in a competitive industry as factor supplies (or prices) shift. Description of the neoclassical production function; Changes in factors that are related to the partial elasticities concepts; Duality relations that hold for the minimum-unit cost function. (Из Ebsco)